A meta-analytic effect analysis: The effect of in-service training on the job performance of school administrators [Bi̇r meta anali̇ti̇k etki̇ anali̇zi̇: Okul yöneti̇ci̇leri̇ni̇n hi̇zmeti̇çi̇ eǧi̇ti̇m almalarinin göreve etki̇si̇] - (:unkn) unknown (My University, 2010)
In this Study, the question "Was there any effect size of school administrators that participated in service training in Turkey, if there exists, in which subjects and what was the direction of the effect size were investigated?" were answered. 16 studies that have the perception of education administrators and have eligible data were included to the meta-analysis research by coding protocol from the pool of 378 studies, which were master and doctoral theses completed between 1997-2006 who participated in the service training and in these studies 2425 school administrators were involved. At the end of the research the mean effect size of education administrators who were participated in the service training was calculated as small. But it was determined that in some studies the effect size of education administrators who participated in the service training was calculated as medium.
Keywords: Education policy; In-service training; Meta-analysis; School administrator